Revistas em tempos de reformas : pensamento jurídico, legislação e política nas páginas dos periódicos de direito (1936-1943) - Mariana de Moraes Silveira (2013)
Taking law journals both as sources and as objects of research, this study aims to analyze the role those periodicals played in Brazilian jurists’ theoretical and, above all, political engagements during the 1930s and 1940s. Over that period, the country underwent a vast process of legal reforms, and as a result most of its major laws were replaced. Despite the dictatorship established in November 1937, and despite campaigns of censorship and political repression, these reforms were never unilaterally imposed by the government. They were developed, on the contrary, in a continuous (and at times tense) dialogue with jurists. The changes in the legal codes that resulted were connected to a variety of issues that law graduates had debated in the preceding years. Law journals were one of the main spaces where the interaction between jurists and the state apparatus took place. They also played a crucial part in the formulation of reformist legal theories. Our intent here is to shed light on the intellectual atmosphere that made such a broad legal reform possible. First, we discuss law periodicals as editorial projects. Our aim is to outline their trajectory in Brazil, and to illuminate the genre’s dynamics in the 1930s and 1940s. We emphasize their role in building a prominent place for jurists in the public scene. We then direct our attention to broader legal debates, emphasizing the so-called “social conception of law”. We discuss critiques to liberalism and the notion that it was necessary to build legal rules that were “adequate to the national reality” in order to overcome Brazil’s “developmental delay”. We also point out a gradual change in jurists’ attitude towards the government. Starting from a position largely receptive to antiliberal ideas and to reformist projects that derived from them, they start to revalue the liberal experience, in a move not disconnected from criticism of the Estado Novo dictatorship. Finally, we analyze the discussions about the legal reforms found in law journals of the period. After describing the general scheme of the project that the government sought to implement beginning in 1930, we develop two case studies, which stand in counterpoint to one another. First, we discuss the broadly praised reform of the Penal Code, achieved in 1940. We then focus on the failed attempt to replace its Civil equivalent, despite the project for a Code of Obligations that was made public in 1941.